2021
DOI: 10.1155/2021/5573469
|View full text |Cite|
|
Sign up to set email alerts
|

Expression and Clinical Significance of miR-146a and Tumor Necrosis Factor Receptor-Associated Factor 6 (TRAF6) in Myasthenia Gravis Patient Serum

Abstract: Objective. To investigate the expression and clinical significance of miR-146a and tumor necrosis factor receptor-associated factor 6 (TRAF6) in myasthenia gravis (MG) patient serum. Methods. The serum of 52 patients with MG and 60 healthy individuals was collected in our hospital. The expression of miR-146a and TRAF6 in serum was measured by real-time PCR (RT-PCR). Comparison among serum miR-146a and TRAF6 mRNA group clinical characteristics and assorted expressions was done with the correlation among the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The miRNA plays a key role in the regulation of the pathogenesis of MG. miRNA is considered to be related to the immune regulation activation mechanism, especially related to the process of T cell response, inflammatory response, and the expression of inflammatory factors. The related research of MG-specific miRNA can provide value for its pathogenesis and treatment [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA plays a key role in the regulation of the pathogenesis of MG. miRNA is considered to be related to the immune regulation activation mechanism, especially related to the process of T cell response, inflammatory response, and the expression of inflammatory factors. The related research of MG-specific miRNA can provide value for its pathogenesis and treatment [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Yan et al. ( 60 ) proposed that overexpressed miR-146a may contribute to the pathogenesis of MG by promoting TRAF6 expression, which could further disrupt Treg function. miR-125a-5p was confirmed to negatively regulate Foxp3, consequently inhibiting the generation of Treg with a great possibility ( 37 ).…”
Section: Mirnas In Mgmentioning
confidence: 99%
“…Recent research outcomes have unveiled a miR-146b-TRAF6-NF-kB-Foxp3 pathway, which plays a crucial role in suppressing Treg proliferation and its inhibitory function (49, 59). Intriguingly, Yan et al (60) proposed that overexpressed miR-146a may contribute to the pathogenesis of MG by promoting TRAF6 expression, which could further disrupt Treg function. miR-125a-…”
Section: Modulation Of Tregs Th17 and Th1mentioning
confidence: 99%
“…Recently, TRAF6 expression was found to be upregulated in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), hyperplastic thymuses and MG patient serum. Studies have demonstrated that miR-146a and TRAF6 exhibit high mRNA expression in peripheral blood mononuclear cells (PBMCs) in MG patients [8,[10][11][12]. In addition, the relationships between TRAF6 expression in peripheral blood B cells and the clinical characteristics of MG patients have rarely been elucidated.…”
Section: Introductionmentioning
confidence: 99%